Markets, morals and development : rethinking economics from a developing country perspective - Mahmud, Wahiduddin (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"This book presents, or rather 're-presents', the intricacies of a developing economy in the light of recent theoretical developments in economics while also providing a fresh perspective on the perceived inadequacies of the discipline in addressing the discontents of the contemporary global economic order. The book argues that there is scope for economics to be a more humane discipline and more relevant to contemporary economic problems by embracing new ideas, including those from other disciplines. It shows how economic concepts including recent theoretical advances can help better understand real life economic phenomena; to rethink the ways of making the market economy address the moral issues of human well-being and social justice and; overall, how the study of economics at an introductory level and public discourses on economic issues can be made more engaging as well as more relevant to the problems of developing countries. Based on public lectures given by the author in Dhaka, and using illustrations from Bangladesh, India and other countries, the book offers an authoritative understanding of diverse economic realities by taking a fresh look at the familiar. Comprehensive and accessible, the book will be of interest to students and researchers of economics, development economics and policy, sociology and business studies as well as journalists, public intellectuals and policymakers in developing countries"--
Introduction -- Thinking Like an Economist, Especially in a Less Developed Country -- The Ethical Basis of Economic Theory and Practice -- Institutions, Morality Norms and Development -- Amartya Sen's Ideas in the Context of Socio-Economic Progress of Bangladesh -- Is there an Economics of Social Business?
Includes bibliographical references and index.
BIGD
Keywords: Economics -- Moral and ethical aspects -- Developing countries; Social justice -- Developing countries; Developing countries -- Economic conditions